Cu-doped TiO2 coating
By doping Cu elements in the titanium dioxide coating and controlling the doping amount, combining solution spraying technology with titanium alkoxide and copper ion precursor, the adhesion and antimicrobial properties of the titanium dioxide coating in the field of electronic materials is solved, and the problem of adhesion and antimicrobial performance of the titanium dioxide coating in the field of electronic materials is achieved. Highly efficient coating curing and excellent mechanical and antimicrobial properties.
Patent Information
- Application Number
- CN202210012586.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-01-07
AI Technical Summary
The existing titanium dioxide coatings have problems such as poor adhesion, poor uniformity and unobvious antimicrobial properties in the application of electronic materials, especially during spraying, and high-temperature sintering will damage the mechanical strength and antimicrobial properties of the substrate. .
Using Cu-doped titanium dioxide coating, the curing temperature is controlled below 420 by controlling the doping amount of Cu element in the coating composition to spray the solution of titanium alkoxide and copper ion precursor compound. °C, a continuous coating based on the O-Ti-O network is formed, avoiding coating in powder form and high temperature sintering.
A coating with excellent mechanical strength and antimicrobial properties is achieved on the substrate, significantly improving the antimicrobial properties while maintaining the adhesion of the coating and the mechanical properties of the substrate.
Smart Images

Figure CN116445014B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a Cu-doped titanium dioxide coating, a coating composition for preparing the coating, a method for preparing the coating composition and an article coated with the coating. Background Art
[0002] In many environmental spaces, including private or public areas of home, community, transportation, office, medical, etc., it is necessary to perform antimicrobial treatment on the surfaces of various articles and equipment, for example, for many frequently used articles such as electronic and electrical equipment with glass, ceramic and steel substrate surfaces.
[0003] Titanium dioxide, especially anatase titanium dioxide, has attracted extensive research from many scholars at home and abroad due to its special photosensitivity. For example, it has been found that titanium dioxide powder will undergo photocatalytic reaction with light of appropriate wavelength to cause activation, and after reacting with atmospheric oxygen and water, a large amount of active oxygen species will be produced, which can play an antimicrobial role. Therefore, titanium dioxide can be widely used in sewage purification and environmental protection applications.
[0004] However, titanium dioxide is often used in powder form. These powders are often used as white pigments in coatings, but if they are directly sprayed, they have problems such as poor adhesion, poor uniformity, and weak antimicrobial properties. This limits its application in the field of electronic materials.
[0005] In recent years, people have tried to modify it by means of Cu doping. For example, in the document "Preparation and photocatalytic performance of Cu-doped TiO2 nanoparticles", Xi-jia YANG et al, Science Direct 25 (2015) 504-509, the use of Cu element doping to modify titanium dioxide nanoparticles was studied to improve its antimicrobial performance to a certain extent. This method studied nanopowder materials with a Cu doping content of 0%-2%, and the powder material was synthesized by a sol-gel method.
[0006] The author of this document believes that if the Cu doping amount reaches or exceeds 2.0%, the photocatalytic performance of titanium dioxide will be reduced to a level similar to that of undoped titanium dioxide, thereby damaging the antimicrobial property. However, the lower Cu doping amount in this document may make it impossible to fully exert the antimicrobial properties of Cu ions themselves. In addition, the sol-gel synthesis method used in this document still prepares a powder product, which is not conducive to the coating and application of titanium dioxide on substrates such as glass, especially for example, spraying. Moreover, the powder sintering temperature in this document is high, reaching 450°C. Although the adhesion may be improved, it may damage the mechanical strength of the substrate such as glass, and also weaken the antimicrobial performance.
[0007] In addition, the prior art also attempts to further improve the photocatalytic activity of titanium dioxide by doping halogens such as F in the titanium dioxide matrix, so that it can be induced to be active with visible light, thereby showing relatively high antibacterial activity. However, the introduction of fluorine dopants complicates the formulation and preparation of titanium dioxide coatings, and does not help improve the bactericidal effect of Cu ions. In addition, the introduction of F ions may also weaken the covalent bonding between the substrate surface and the coating, weakening the bonding strength between the two, thereby affecting the adhesion of the coating on the substrate surface and the durability of the antibacterial surface.
[0008] Therefore, there is still a need to further improve the antimicrobial properties of titanium dioxide coatings, especially Cu-doped titanium dioxide coatings, while maintaining or improving the mechanical properties and adhesion of the titanium dioxide coatings. In particular, it is also desirable to be able to produce a titanium dioxide coating composition suitable for spray application rather than powder coating. Summary of the invention
[0009] Therefore, the first aspect of the present application relates to a Cu-doped titanium dioxide coating, which comprises a titanium dioxide base material and a Cu element doped therein, characterized in that the doping amount of the Cu element is 4-25 mol % based on the entire coating after curing.
[0010] A second aspect of the present application relates to a coating composition for coating on a substrate, comprising 5.5-25.0 wt %, preferably 6.5-22.0 wt %, such as 8.0-15.0 wt % of titanium alkoxide, 0.15-4.5 wt %, for example 0.20-4.0 wt % or 0.30-3.5 wt % of a copper ion precursor, an acid-containing stabilizer and an alcohol-containing diluent, based on the total weight of the coating composition excluding water.
[0011] The third aspect of the present application relates to a method for preparing a coating composition, in particular the coating composition as described above, comprising: (1) preparing a solution comprising a titanium alkoxide and a diluent; (2) preparing a solution comprising a copper precursor compound and a diluent, and (3) mixing the two solutions to obtain a composition precursor mixture, wherein the pH of the solution is controlled within the range of 0.1-6 in the above steps (1) and (2), and substantially no water is contained in the solution in steps (1) and (2).
[0012] The fourth aspect of the present application relates to a method for preparing a titanium dioxide coating on a substrate, comprising: (1) applying the coating composition according to the second aspect or the coating composition prepared according to the method described in the third aspect to the substrate, and (2) raising the temperature to cure the applied coating composition.
[0013] A fifth aspect of the present application relates to an article coated with the Cu-doped titanium dioxide coating according to the present invention.
[0014] The inventors have found that the coating composition according to the present invention can be advantageously applied as a solution rather than a powder suspension (e.g., a powder prepared by a sol-gel method and then formulated into a coatable powder suspension) and is therefore suitable for spraying on a substrate. In addition, since the coating composition can be baked at a lower temperature, such as a temperature below 420° C., after application, the cured titanium dioxide coating maintains excellent mechanical strength, such as wear resistance, while still having excellent adhesion. At the same time, since the coating can contain a higher content of Cu + ions, so its antimicrobial properties can be significantly improved.
[0015] The Cu-doped titanium dioxide coating according to the present invention is based on titanium dioxide. The technical staff understands that the so-called "base" refers to the non-volatile film-forming part of the coating, which constitutes the matrix phase of the coating. The film composed of titanium dioxide is particularly suitable for adhesion to substrates such as glass, ceramics and steel.
[0016] In the context of the present application, the "Cu-doped titanium dioxide coating", "titanium dioxide coating" refers to a coating formed by curing a liquid coating composition for coating on a substrate after application. In this process, the titanium alkoxide in the coating composition is hydrolyzed under elevated temperature conditions to form a titanium dioxide base material. In particular, on the substrate, the titanium dioxide coating of the present invention is in the form of a continuous coating composed of an O-Ti-O network rather than a powder coating composed of discrete TiO2 particles or powders.
[0017] In a preferred embodiment of the present invention, the titanium dioxide coating is composed of a matrix phase and doping ions, the matrix phase is composed of an O-Ti-O network, and the doping ions are basically composed of Cu ions, and the doping amount of the Cu element is 4-25 mol%, such as 6-20 mol% or 8-16 mol%, based on Cu and the entire coating. The "Cu ions" include monovalent Cu ions (Cu + ) and divalent ions (Cu 2+ ).
[0018] Titanium alkoxide (also known as titanate) is a compound having the general formula Ti(-OR)4 structure, wherein R represents a linear or branched C1-C8, preferably C1-C4 alkyl group. Examples of titanium alkoxide suitable for the present invention include titanium methoxide, titanium ethoxide, titanium propoxide, titanium isopropoxide, titanium butoxide, titanium isobutoxide, etc., preferably selected from titanium isopropoxide, titanium butoxide and titanium isobutoxide, in particular titanium tetrabutoxide (also known as tetrabutyl titanate).
[0019] It is known that copper ions, especially Cu + It has a good antimicrobial effect, so it is beneficial to incorporate it into the titanium dioxide coating. Copper ions can be added to the solution of titanium alkoxide in the form of its precursor, and then doped into the titanium dioxide structure during high temperature curing.
[0020] The copper ion precursor itself is not particularly limited. According to a preferred embodiment of the present invention, the copper ion precursor compound includes copper nitrate, carboxylates such as acetate, formates, etc., sulfates and various hydrates thereof. Preferably, copper nitrate and its hydrates can be used as copper ion precursor compounds. In the present invention, copper halides such as fluorides or chlorides are not suitable as copper ion precursor compounds, because it has been found that the presence of halogen elements may inhibit the formation of covalent crosslinks between the coating and the substrate surface, thereby affecting the adhesion of the coating and affecting the antibacterial effect.
[0021] In the titanium dioxide coating of the present invention, copper ions should be doped into the final cured titanium dioxide coating at a ratio of 4-25 mol%. If the doping amount of copper ions is less than 4 mol%, the antimicrobial effect may not be fully exerted; while if the doping amount of copper ions is higher than 25 mol%, it will affect the doping of copper ions into the titanium dioxide matrix, causing some CuO crystals to precipitate, which will not only affect the surface activity of the titanium dioxide coating and the overall performance of the material, but also affect the appearance and coating effect of the coating.
[0022] It is also found that in the titanium dioxide coating of the present invention, Cu + / Cu 2+The ratio can be greater than 1.1, preferably greater than 1.3, which is beneficial for further improving the antimicrobial performance. In the prior art (such as the sol-gel method), the sintering temperature of the coating is usually high, such as 450°C or higher, which will cause Cu 2+ In addition, the Cu doping amount in the titanium dioxide coating prepared by the prior art method is usually very low, and if the Cu doping amount is increased (for example, more than 3 mol%), it will also lead to Cu 2+ The proportion of ions increased significantly.
[0023] Preferably, the titanium dioxide coating of the present invention does not contain halogen, especially F as a doping ion, so as to avoid the adverse effects of F doping. It is also preferred that, from the perspectives of coloring, oxidation resistance, toxicity and availability, the titanium dioxide coating of the present invention substantially only contains Cu element as a doping ion. This means that the Cu element can account for more than 99% of the doped metal ions, such as 99.5% or 99.8% or 99.9% or 100%, and other heavy metal ions such as iron, manganese, zinc, lead, tin, mercury, cadmium, silver, etc. are not intentionally added. If present, these other heavy metal ions are preferably present only in an amount not exceeding 0.5 mol%, more preferably not exceeding 0.1 mol%, or are absent.
[0024] The titanium dioxide coating according to the present invention can be prepared from a coating composition as its precursor material. Those skilled in the art can select titanium alkoxide and copper precursor compound and their amounts in a suitable coating composition according to their own chemical knowledge and common sense of production practice to obtain a titanium dioxide coating with a final required Cu doping amount.
[0025] Therefore, as described above, the present invention also relates to a coating composition for coating on a substrate, which comprises 5.5-25.0 wt%, preferably 6.5-22.0 wt%, such as 8.0-15.0 wt% of titanium alkoxide, 0.15-4.5 wt%, for example 0.20-4.0 wt% or 0.30-3.5 wt% of a copper ion precursor, an acid-containing stabilizer and an alcohol-containing diluent, based on the total weight of the coating composition without water.
[0026] In order to prepare the coating composition, the following method is required, which comprises: (1) preparing a solution comprising a titanium alkoxide and a diluent; (2) preparing a solution comprising a copper precursor compound and a diluent, and (3) mixing the above two solutions to obtain a composition precursor mixture, wherein the pH of the solution is controlled within the range of 0.1-6 in the above steps (1) and (2), and substantially no water is contained in the solutions of steps (1) and (2).
[0027] The inventors of the present application have found that it is critical to control the pH in the range of 0.1-6, preferably 0.3-5.4, for example, about 0.5-4.5 or 0.9-4.1 during the preparation of the solution of titanium alkoxide and copper precursor compound, because this can form a very stable final mixed solution without forming a sol, thereby making it possible to prepare a coating composition suitable for spray application, especially a concentrate or an aqueous solution thereof. Thus, because a solution is formed instead of a sol, there is no need in the present invention to perform a drying process at an elevated temperature to form it into a gel and / or further sinter it (for example, at a temperature above 425° C., such as 450° C.) into a powder, as required by a conventional sol-gel method.
[0028] In addition, by controlling the pH value during the solution process of the titanium alkoxide and the copper precursor compound as described above, the following advantages can be achieved:
[0029] (i) The copper precursor compound in the prepared coating composition can be stably present in the solution at a higher concentration, and a higher concentration of Cu ions, especially Cu ions, can be incorporated into the final titanium dioxide coating. + ion.
[0030] (ii) The ability to generally stabilize the resulting titanium dioxide coating solution against settling and sedimentation, thereby making it particularly suitable for application to substrates such as glass, ceramics and steel by spray application.
[0031] (iii) Effectively protect spraying equipment to ensure the feasibility and stability of operation.
[0032] Steps (1) and (2) can be performed in any order, but the pH of the solution must be controlled in the range of 0.1-6 in these two steps. Advantageously, the pH value is still maintained in the required range in the mixing step (3), preferably before application. The pH value can be controlled by those methods known to technicians to adjust the pH value, such as selecting a solvent or diluent with a suitable pH value to dissolve the titanate and the Cu precursor compound, or adding a suitable pH adjuster.
[0033] In addition, water or materials containing water (except water of crystallization) should not be added or used as much as possible during the dissolution process of steps (1) and (2), so that the solutions obtained in steps (1) and (2) are substantially free of water. Preferably, in step (3) of mixing the solutions obtained in (1) and (2) and before the final dilution with water for application such as spraying, the obtained mixed solution or concentrate is also substantially free of water. During the dissolution process, the addition of water is not conducive to the long-term storage of the mixed solution and is prone to cause precipitation, especially precipitation of titanium. In the present application, "substantially free of water" means containing less than 0.1wt%, preferably less than 0.05wt% or less than 0.01wt% of water based on the total weight of the solution, or completely free of water.
[0034] The mixing operation of step (3) is not particularly limited, and includes adding the titanium alkoxide solution to the prepared copper precursor compound solution, or vice versa. After the two solutions are in contact, they are fully stirred to obtain a uniform mixed solution.
[0035] Steps (1) to (3) or the preparation process of the coating composition comprising these steps may be carried out at ambient temperature such as room temperature, for example, 10-30° C. or 15-25° C. Preferably, the dissolving and mixing may be carried out with stirring.
[0036] The diluent used in steps (1) to (3) should be able to help the titanium alkoxide and the copper precursor compound form a stable solution, and preferably contains an alcohol.
[0037] Suitable alcohols include aliphatic alcohols, preferably C1-C8, more preferably C2-C6 alcohols, such as ethanol. Advantageously, alcohols with a purity higher than 99% or 99.5% or anhydrous forms of alcohols are used to dissolve titanium alkoxide and copper precursor, because the presence of water will cause a hydrolysis reaction of titanium alkoxide, which is not conducive to the stable progress of the subsequent spraying process.
[0038] The amount of alcohol used is advantageously in the range of 20.0-90.0 wt%, preferably 24.0-86.0 wt%, for example 33.0-65.0 wt%, based on the total weight of the coating composition excluding water.
[0039] Generally, in addition to better controlling the pH value within the required range, in order to stabilize the solution and facilitate storage and transportation, it is also preferred to add a stabilizer, especially an acid-containing stabilizer, in at least one of steps (1) to (3). Suitable stabilizers include acids selected from, for example, organic acids or non-oxidizing inorganic acids, especially mono- or di-carboxylic acids, such as C1-C8 or C1-C6 aliphatic acids or C6-C12 aromatic carboxylic acids, such as acetic acid, propionic acid, butyric acid, oxalic acid, citric acid, benzoic acid, etc., preferably acetic acid such as glacial acetic acid, or hydrochloric acid, sulfuric acid or nitric acid. It is preferred to add an acid-containing stabilizer in steps (1) and (2) as described above.
[0040] The amount of acid used is advantageously in the range of 1.0-70.0 wt%, preferably 1.3-67.0 wt%, for example 9.0-55.0 wt%, based on the total weight of the coating composition excluding water.
[0041] In addition, acetylacetone may be advantageously added in at least one of steps (1) to (3), which facilitates the dissolution of possible precipitation, thereby helping to stabilize the solution. If used, the amount of acetylacetone may advantageously be in the range of 0.5-2.3 wt%, preferably 0.7-2.1 wt% or 1.5 wt%, based on the total weight of the coating composition excluding water. If necessary, acetylacetone is preferably added in step (3).
[0042] In an exemplary embodiment, when preparing the precursor of the titanium dioxide coating, i.e., the coating composition to be applied to the substrate, both an alcohol (especially ethanol) as a solvent and a stabilizer containing an acid (especially glacial acetic acid) are used, and the ratio of the amount of all alcohols added to the acid during the formulation process is in the range of a volume ratio of 75:1 to 1:2, such as 50:1 to 1:1, 30:1 to 1:1, 10:1 to 1:1, 5:1 to 2:1. Such a ratio is conducive to dissolving titanium alkoxide and copper precursor compounds and controlling the pH value within the required range.
[0043] It is preferred when the acid, alcohol and optionally acetylacetone are used within the above-mentioned amount range, because this is very beneficial for controlling and maintaining the required pH value, thereby maintaining the stability of the solution.
[0044] Also preferably, the ratio of total solvent (including stabilizer and diluent) to solute (including titanium alkoxide and copper ion precursor compound) is greater than 5:1 by volume, based on the total weight of the non-aqueous titanium dioxide coating mixture.
[0045] The coating composition according to the present invention can be formulated into a concentrate containing no water or only a small amount of water (such as less than 1wt%, 0.5wt%, 0.1wt% or 0.02wt%) and an aqueous solution after dilution with water. In an advantageous embodiment, after dilution with water, especially after dilution with water before application such as spraying, the coating composition can be formulated to contain 0.8-1.6wt%, for example 0.9-1.2wt% of titanium alkoxide such as Ti(OC4H9)4, 0.02-1.4wt%, preferably 0.05-1.2wt% of copper ion precursor such as Cu(N03)2·3H20, an acid-containing stabilizer and an alcohol-containing diluent, based on the total weight of the coating composition after adding water.
[0046] Subsequently, the coating composition can be applied to the substrate (preferably by spraying, dipping, printing and vapor deposition, etc., particularly preferably spraying), and then the coating composition is cured at an elevated temperature to obtain a high concentration of Cu-doped titanium dioxide coating. In this process, the prepared coating composition can be diluted with water before being applied to the substrate as needed to facilitate subsequent coating, such as spraying. For example, after a uniform mixture of water-free titanium alkoxide and copper precursor solution is obtained by steps (1)-(3), an appropriate amount of water is added to dilute it. For example, 60-98, such as 70-96 or 85-95% by weight of water can be added, based on the total weight of the coating composition after dilution with water.
[0047] Unlike the sol-gel method of the prior art, the coating composition according to the present invention does not need to be dried or boiled at elevated temperature to obtain a gel after the substantially anhydrous solution containing titanium alkoxide and copper precursor compound is prepared. They can be applied to the substrate in the form of a solution after dilution with water, especially sprayed on the substrate, very stably.
[0048] In addition, after the coating composition according to the present invention is applied as a solution onto a substrate, such as by spraying, the coating composition can be directly cured and crystallized at an elevated temperature without a drying step. Therefore, the present invention also relates to a method for preparing a titanium dioxide coating on a substrate, comprising: (1) applying the coating composition as described above or the coating composition prepared according to the method as described above onto a substrate, and (2) raising the temperature to cure the applied coating composition.
[0049] Here, curing can be carried out in a device suitable for baking to form anatase titanium dioxide coating. An advantage of the coating composition of the present invention is that it can be cured at a relatively low temperature, such as below 450°C, preferably at a temperature of 350 to 420°C, which is very beneficial for maintaining the strength of the substrate and maintaining the antimicrobial properties of the coating.
[0050] As mentioned above, preferably, the prepared coating composition is applied to the substrate in the form of a solution (preferably by spraying).
[0051] Substrates suitable for applying the titanium dioxide coating of the present invention include glass, ceramics, various inorganic composite materials, and the like.
[0052] The antimicrobial performance of the titanium dioxide coating according to the present invention is excellent. It has been found that the antimicrobial efficiency of the titanium dioxide coating according to the present invention against bacteria (such as Escherichia coli, Staphylococcus aureus, etc.) and viruses (such as human coronavirus, etc.) can reach more than 99.9%.
[0053] In addition, the present application also relates to articles comprising the titanium dioxide coating of the present invention, and these suitable articles include display screens in public places, computer screens, mobile phone screens, touch surfaces of electronic equipment in hospitals, etc.
[0054] Therefore, this application relates to the following solutions:
[0055] 1. A Cu-doped titanium dioxide coating, comprising a titanium dioxide base material and a Cu element doped therein, wherein the doping amount of the Cu element is 4-25 mol % based on the entire coating after curing.
[0056] 2. The titanium dioxide coating according to Scheme 1 is characterized in that the doping amount of the Cu element in the coating is 8-16 mol%.
[0057] 3. The titanium dioxide coating according to any of the above solutions is characterized in that the Cu + / Cu 2+ The ratio is greater than 1.1, preferably greater than 1.3.
[0058] 4. The titanium dioxide coating according to any of the aforementioned schemes is characterized in that other heavy metal ions except Cu, such as iron, silver, manganese, zinc, lead, tin, mercury, and cadmium, are present in the coating in an amount not exceeding 0.5 mol%, more preferably not exceeding 0.1 mol%.
[0059] 5. The titanium dioxide coating according to any of the aforementioned solutions is characterized in that the coating does not contain halogen elements, especially F.
[0060] 6. The titanium dioxide coating according to any of the preceding schemes is characterized in that the coating is in the form of a continuous coating based on an O-Ti-O network.
[0061] 7. A coating composition comprising 5.5-25.0 wt%, preferably 6.5-22.0 wt%, such as 8.0-15.0 wt% of titanium alkoxide, 0.15-4.5 wt%, such as 0.20-4.0 wt% or 0.30-3.5 wt% of a copper ion precursor, an acid-containing stabilizer and an alcohol-containing diluent, based on the total weight of the coating composition excluding water.
[0062] 8. The coating composition according to Scheme 7 is characterized in that the titanium alkoxide is selected from titanium methoxide, titanium ethoxide, titanium propoxide, titanium isopropoxide, titanium butoxide, titanium isobutoxide, etc., preferably selected from titanium isopropoxide, titanium butoxide and titanium isobutoxide, in particular tetrabutyl titanate.
[0063] 9. The coating composition according to Scheme 7 or 8 is characterized in that the copper ion precursor compound is selected from copper nitrates, carboxylates such as acetates and formates, sulfates and various hydrates thereof, preferably selected from copper nitrate and its hydrates.
[0064] 10. A coating composition according to any one of Schemes 7 to 9, characterized in that the alcohol is selected from aliphatic alcohols, preferably C1-C8, more preferably C2-C6 alcohols such as ethanol, preferably alcohols with a purity higher than 99% or anhydrous forms of alcohols, more preferably anhydrous ethanol.
[0065] 11. A coating composition according to any one of Schemes 7 to 10, characterized in that the amount of the alcohol is in the range of 20-90 wt%, preferably 24.0-86.0 wt%, for example 33.0-65.0 wt%, based on the total weight of the coating composition excluding water.
[0066] 12. A coating composition according to any one of Schemes 7 to 11, characterized in that the acid is selected from non-oxidizing inorganic acids and mono- or di-carboxylic acids, such as C1-C8 or C1-C6 aliphatic acids or C6-C12 aromatic carboxylic acids, such as acetic acid, propionic acid, butyric acid, oxalic acid, citric acid, benzoic acid, etc., preferably acetic acid such as glacial acetic acid, or hydrochloric acid, sulfuric acid or nitric acid.
[0067] 13. A coating composition according to any one of Schemes 7 to 12, characterized in that the amount of the acid is in the range of 1.0-70.0 wt%, preferably 1.3-67.0 wt%, for example 9.0-55.0 wt%, based on the total weight of the coating composition excluding water.
[0068] 14. The coating composition according to any one of schemes 7 to 12, characterized in that the composition further comprises acetylacetone, preferably in an amount in the range of 0.5-2.3 wt%, preferably 0.7-2.1 wt% or 1.5 wt%, based on the total weight of the coating composition excluding water.
[0069] 15. A coating composition according to any one of Schemes 7 to 14, characterized in that the ratio of the alcohol to the acid is in the volume ratio range of 10:1 to 1:2, for example, 8:1 to 1:1 or 5:1 to 2:1.
[0070] 16. The coating composition according to any one of Schemes 7 to 15, characterized in that the coating composition is in the form of a concentrate and an aqueous solution after dilution with water.
[0071] 17. A coating composition according to any one of Schemes 7 to 16, characterized in that the coating composition comprises 0.8-1.6 wt%, for example 0.9-1.2 wt%, of titanium alkoxide, 0.02-1.4 wt%, preferably 0.05-1.2 wt% of a copper ion precursor, an acid-containing stabilizer and an alcohol-containing diluent, and 60-98 wt% of water, based on the total weight of the coating composition.
[0072] 18. A method for preparing a coating composition, in particular a coating composition according to any one of Schemes 7 to 17, comprising: (1) preparing a solution comprising a titanium alkoxide and a diluent; (2) preparing a solution comprising a copper precursor compound and a diluent, and (3) mixing the two solutions to obtain a composition precursor mixture, wherein the pH of the solution is controlled within the range of 0.1-6 in the above steps (1) and (2), and substantially no water is contained in the solutions of steps (1) and (2).
[0073] 19. The method according to Scheme 18 is characterized in that a stabilizer, in particular a stabilizer containing an acid, is added in at least one of steps (1) to (3), in particular steps (1) and (2).
[0074] 20. The method according to Scheme 18 or 19, characterized in that acetylacetone is added, especially in step (3).
[0075] 21. A method for preparing a titanium dioxide coating on a substrate, comprising: (1) applying a coating composition as described in Scheme 7 or a coating composition prepared according to the method as described in Scheme 18 to a substrate, and (2) raising the temperature to cure the applied coating composition.
[0076] 22. A method according to claim 21, wherein curing is carried out at a temperature below 450°C, preferably 350 to 420°C.
[0077] 23. The method according to claim 21 or 22, wherein the coating composition is applied to the substrate by spraying in the form of an aqueous solution.
[0078] 24. A method according to any one of Schemes 21 to 23, wherein the substrate comprises glass, ceramic and / or various inorganic composite materials.
[0079] 25. Articles comprising the titanium dioxide coating as described in Scheme 1, wherein the articles include display screens in public places, computer screens, mobile phone screens, and touch surfaces of electronic equipment in hospitals. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1a Shown are the appearance of the substrate surface and coating of Example Ex1 before and after sintering;
[0081] Figure 1b Shown are the appearance of the substrate surface and coating of Example Ex1 before and after rubbing;
[0082] Figure 2 Shown are XPS graphs of copper content in the coatings of Examples Ex1 to Ex4, wherein number A corresponds to Example Ex4, number B corresponds to Ex2, number C corresponds to Ex3 and number D corresponds to Ex1;
[0083] Figure 3 Shown are the appearance of the substrate surface and coating of Example Ex4 after sintering. Example
[0084] The present application is further described below in conjunction with the examples. However, the present application is not limited to the following examples. In addition, the percentage data and proportion ratios in the present application specification are all measured by weight unless otherwise clearly stated.
[0085] Ingredients
[0086] name illustrate Tetrabutyl titanate Purity>98.0%, purchased from Sinopharm Chemical Reagent Co., Ltd. Copper Nitrate Trihydrate Purity>99.0%, analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd. Anhydrous ethanol Purity>99.8%, superior grade, purchased from Sinopharm Chemical Reagent Co., Ltd. glacial acetic acid Purity>99.5%, analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd. Acetylacetone Purity>99.0%, analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0087] Preparation Example
[0088] Example 1
[0089] First, 10 ml of tetrabutyl titanate was added dropwise to 70 ml of solvent (a mixture of anhydrous ethanol and glacial acetic acid in a ratio of 1:1) at a volume ratio of 1:7, and the mixture was stirred with a glass rod to obtain a tetrabutyl titanate solution. Subsequently, 0.70 g of copper nitrate trihydrate solid was dissolved in 22 ml of a solvent in a ratio of 1:1 of anhydrous ethanol and glacial acetic acid, and the mixture was stirred until the solid was fully dissolved to obtain a copper nitrate solution. The copper nitrate solution was added dropwise to the tetrabutyl titanate solution, and 1 ml of acetylacetone was added dropwise after stirring, and stirring was continued until the solution was fully mixed to obtain a precursor solution of a titanium dioxide coating.
[0090] Then, the obtained titanium dioxide coating precursor solution (coating composition solution) was diluted to 1000 ml by adding water, and the diluted solution was directly sprayed on a glass substrate and baked at 400° C. for 1 h to obtain glass with a Cu-doped TiO2 coating.
[0091] The matrix phase of the TiO2 coating obtained was TiO2, the Cu ion doping amount was measured to be 8.92 mol%, and the Cu 1 + :Cu 2+ =1.64.
[0092] Example 2
[0093] The steps of Example 1 were repeated except that 0.22 g of copper nitrate trihydrate was used.
[0094] The matrix phase of the TiO2 coating obtained was TiO2, the Cu ion doping amount was measured to be 3.13 mol%, and the Cu 1 + :Cu 2+ =1.37.
[0095] Example 3
[0096] The steps of Example 1 were repeated except that 1.16 g of copper nitrate trihydrate was used.
[0097] The matrix phase of the TiO2 coating obtained was TiO2, the Cu ion doping amount was measured to be 14.07 mol%, and the Cu ion doping amount in the product was measured to be 14.07 mol%. 1+ :Cu 2+ =1.18.
[0098] Example 4
[0099] The procedure of Example 1 was repeated except that 5.82 g of copper nitrate trihydrate was used.
[0100] The matrix phase of the obtained TiO2 coating is TiO2, and the Cu ion doping amount is measured to be 46.04 mol%.
[0101] Example 5
[0102] The steps of Example 1 were repeated except that 0.07 g of copper nitrate trihydrate was used.
[0103] The matrix phase of the obtained TiO2 coating is TiO2, and the Cu ion doping amount is measured to be 1 mol%.
[0104] Example 6
[0105] The steps of Example 1 were repeated, except that glacial acetic acid was not added during both dissolution processes. The solution was unstable and a small amount of white precipitate appeared. Therefore, the subsequent application and curing steps were not performed.
[0106] Example 7
[0107] The steps of Example 1 were repeated, except that anhydrous ethanol was not added to the solvent, and tetrabutyl titanate was directly dissolved in glacial acetic acid. In the first step of the experiment, when tetrabutyl titanate was added dropwise to the solvent and mixed and stirred, the solution emulsified, and white precipitation was visible after standing, and a strong pungent odor was smelled. Therefore, the subsequent application and curing steps were no longer performed.
[0108] Example 8
[0109] The steps of Example 1 were repeated, except that the volume ratio of ethanol to glacial acetic acid in the solvent was 70:1. After the solution was mixed evenly, it was observed to be a transparent solution without precipitation.
[0110] Then, the obtained titanium dioxide coating precursor solution (coating composition solution) was diluted to 1000 ml by adding water, and the diluted solution was directly sprayed on a glass substrate and baked at 400° C. for 1 h to obtain glass with a Cu-doped TiO2 coating.
[0111] Example 9
[0112] The steps of Example 1 were repeated, except that the ratio of ethanol to glacial acetic acid in the solvent was 1:70. In the first step of the experiment, when tetrabutyl titanate was added dropwise to the solvent for dissolution, the solution was emulsified, and white precipitation was visible after standing. Therefore, the subsequent application and curing steps were not performed.
[0113] The pH values in steps (1) and (2) in the above examples were measured and recorded in the table below.
[0114] Performance Testing
[0115] The glass with Cu-doped TiO2 coating prepared as described above was subjected to performance tests as follows, and the test results are listed in Table 1.
[0116] Cu content in coating
[0117] XPS test confirmed the Cu content.
[0118] The XPS equipment manufacturer is ThermoFisher, model: Thermo Scientific K-Alpha. The test conditions used are as follows: the vacuum degree of the analysis chamber is about 5*10-7mbar; the X-ray source is a monochromatic AlKa source (Mono AlKa), energy 1486.6eV, voltage 12KV, beam current: 6mA, and the analyzer scanning mode is CAE.
[0119] Antimicrobial:
[0120] Guangdong Microbiological Analysis and Testing Center was commissioned to conduct antimicrobial testing. The antimicrobial test reference standard is ISO27447:2009, and the human coronavirus test reference standard is ISO18061-2014.
[0121] The antiviral test results of human coronavirus (HCoV-229E) (ATCC VR-740) of Ex1 sample can be found in Report No. (Report №.) 2021FM05821R01D; the antibacterial test results of Escherichia coli virus and Staphylococcus aureus can be found in Report No. (Report №.) 2021FM02989R01D
[0122] The results of Ex5's antibacterial tests on Escherichia coli virus and Staphylococcus aureus can be found in Report No. 2020FM35046R01D.
[0123] The Ex1 sample according to the present invention is significantly superior to the Ex5 sample in terms of the tested antimicrobial properties.
[0124] Friction resistance:
[0125] Refer to the enterprise standard: ES601150, where the test instrument is a general steel wool friction machine, the friction number is 3000 cycles, the load is 1kg, the friction medium is EF74 rubber, the friction stroke is 5cm, and the speed is 60cycle / min. Then use a microscope to observe whether the spray layer is obviously detached after friction. If the detached area is greater than 20%, it is a fail.
[0126] Chemical resistance:
[0127] Reference standard: ASTM-D-1308-02(1993)
[0128] Chemical testing conditions:
[0129] Soak the cured test surface with chemical Formula 409 multi-surface cleaner, ammonia, isopropyl alcohol (IPA), acetone, alcohol, hydrochloric acid and bleach for 24 hours. After removing the immersion liquid, clean the liquid residue and observe whether there is no obvious change on the surface of the test product, whether the coating has fallen off, and whether there is no obvious change in the optical properties. If the measured change rate of haze and transmittance before and after is less than 20%, it is evaluated as Pass.
[0130] During the immersion period, in order to prevent the volatilization and loss of chemicals, it is necessary to soak a cotton pad or dust-free cloth and cover it on the test surface. Use a watch glass or other container to cover and soak it without protection. Use tape to seal the container around to prevent the chemical liquid from evaporating or volatilizing.
[0131] Appearance:
[0132] Refer to the company's optical standard ES601048 and observe with the naked eye. Compared with the sample without coating, if the coating after sintering has no obvious color difference and the coating surface is uniform, and the antibacterial layer is observed under a microscope as clear bubbles attached to the surface of the substrate, it is evaluated as Pass; if the coating after sintering has obvious color difference or obvious granularity, it is evaluated as Fail.
[0133] Table 1 Coating composition and performance test results
[0134]
[0135] NA* indicates not tested.
Claims
1. A Cu-doped titanium dioxide coating comprising a titanium dioxide base material and a Cu element doped therein, characterized in that: The doping amount of the Cu element is 4-25 mol% based on the entire coating after curing, and the Cu in the coating is + / Cu 2+ The ratio is greater than 1.1, wherein the coating does not contain halogen elements and is in the form of a continuous coating composed of an O-Ti-O network.
2. The titanium dioxide coating according to claim 1, characterized in that The doping amount of the Cu element in the coating is 8-16 mol%.
3. The titanium dioxide coating according to claim 1, characterized in that Coating Cu + / Cu 2+ The ratio is greater than 1.
3.
4. The titanium dioxide coating according to any one of the preceding claims 1 to 3, characterized in that Other heavy metal ions except Cu are present in the coating in an amount of not more than 0.5 mol %.
5. The titanium dioxide coating according to claim 4, characterized in that The other heavy metal ions except Cu are selected from iron, silver, manganese, zinc, lead, tin, mercury or cadmium.
6. The titanium dioxide coating according to claim 4, characterized in that Other heavy metal ions except Cu are present in the coating in an amount of not more than 0.1 mol %.
7. A coating composition for preparing a Cu-doped titanium dioxide coating as claimed in claim 1, comprising 5.5-25.0 wt% of a titanium alkoxide, 0.15-4.5 wt% of a copper ion precursor compound, an acid-containing stabilizer and an alcohol-containing diluent, based on the total weight of the coating composition without water; wherein the ratio of the alcohol to the acid is in the range of 10:1 to 1:2 by volume.
8. The coating composition according to claim 7, characterized in that It contains 6.5-22.0 wt% of titanium alkoxide.
9. The coating composition according to claim 7, characterized in that It contains 8.0-15.0 wt% of titanium alkoxide.
10. The coating composition according to claim 7, characterized in that It contains 0.20-4.0 wt% of a copper ion precursor compound.
11. The coating composition according to claim 7, characterized in that It contains 0.30-3.5 wt% of a copper ion precursor compound.
12. The coating composition according to claim 7, characterized in that The titanium alkoxide is selected from titanium methoxide, titanium ethoxide, titanium propoxide, titanium isopropoxide, titanium butoxide, and titanium isobutoxide.
13. The coating composition according to claim 7, characterized in that The titanium alkoxide is selected from titanium isopropoxide, titanium butoxide and titanium isobutoxide.
14. The coating composition according to claim 7, characterized in that The titanium alkoxide is selected from tetrabutyl titanate.
15. The coating composition according to any one of claims 7 to 14, characterized in that The copper ion precursor compound is selected from copper nitrate, carboxylate, sulfate and various hydrates thereof.
16. The coating composition according to claim 15, characterized in that The copper ion precursor compound is selected from the group consisting of copper acetate and formates.
17. The coating composition according to claim 15, characterized in that The copper ion precursor compound is selected from copper nitrate and its hydrate.
18. The coating composition according to any one of claims 7 to 14, characterized in that The alcohol is selected from aliphatic alcohols.
19. The coating composition according to claim 18, characterized in that The alcohol is selected from C1-C8 alcohols.
20. The coating composition according to claim 18, characterized in that The alcohol is selected from C2-C6 alcohols.
21. The coating composition according to claim 18, characterized in that The alcohol is selected from ethanol.
22. The coating composition according to claim 18, characterized in that The alcohol is selected from alcohols with a purity higher than 99% or anhydrous forms of alcohols.
23. The coating composition according to claim 18, characterized in that The alcohol is selected from anhydrous ethanol.
24. The coating composition according to any one of claims 7 to 14, characterized in that The alcohol is used in an amount ranging from 20 to 90 wt %, based on the total weight of the coating composition excluding water.
25. The coating composition according to any one of claims 7 to 14, characterized in that The alcohol is used in an amount ranging from 24.0 to 86.0 wt %, based on the total weight of the coating composition excluding water.
26. The coating composition according to any one of claims 7 to 14, characterized in that The alcohol is used in an amount ranging from 33.0 to 65.0 wt %, based on the total weight of the coating composition excluding water.
27. The coating composition according to any one of claims 7 to 14, characterized in that The acid is selected from non-oxidizing inorganic acids and mono- or di-carboxylic acids.
28. The coating composition according to claim 27, characterized in that The acid is selected from C1-C8 aliphatic acids or C6-C12 aromatic carboxylic acids.
29. The coating composition according to claim 27, characterized in that The acid is selected from C1-C6 aliphatic acids.
30. The coating composition according to claim 27, characterized in that The acid is selected from acetic acid, propionic acid, butyric acid, oxalic acid, citric acid, benzoic acid, hydrochloric acid, sulfuric acid or nitric acid.
31. The coating composition according to claim 27, characterized in that The acid is selected from acetic acid.
32. The coating composition according to claim 27, characterized in that The acid is selected from glacial acetic acid.
33. The coating composition according to any one of claims 7 to 14, characterized in that The acid is used in an amount ranging from 1.0 to 70.0 wt %, based on the total weight of the coating composition excluding water.
34. The coating composition according to any one of claims 7 to 14, characterized in that The acid is used in an amount ranging from 1.3 to 67.0 wt %, based on the total weight of the coating composition excluding water.
35. The coating composition according to any one of claims 7 to 14, characterized in that The acid is used in an amount ranging from 9.0 to 55.0 wt %, based on the total weight of the coating composition excluding water.
36. The coating composition according to any one of claims 7 to 14, characterized in that The composition also includes acetylacetone.
37. The coating composition according to claim 36, characterized in that The composition further comprises acetylacetone in an amount ranging from 0.5 to 2.3 wt %, based on the total weight of the coating composition excluding water.
38. The coating composition according to claim 36, characterized in that The composition further comprises acetylacetone in an amount ranging from 0.7 to 2.1 wt %, based on the total weight of the coating composition excluding water.
39. The coating composition according to claim 36, characterized in that The composition further comprises acetylacetone in an amount ranging from 0.7 to 1.5 wt %, based on the total weight of the coating composition excluding water.
40. The coating composition according to any one of claims 7 to 14, characterized in that The ratio of the alcohol to the acid is in the range of 8:1 to 1:1 by volume.
41. The coating composition according to any one of claims 7 to 14, characterized in that The ratio of the alcohol to the acid is in the range of 5:1 to 2:1 by volume.
42. The coating composition according to any one of claims 7 to 14, characterized in that The coating composition is in the form of a concentrate or an aqueous solution after dilution with water.
43. The coating composition according to any one of claims 7 to 14, characterized in that The coating composition comprises 0.8-1.6 wt % of titanium alkoxide, 0.02-1.4 wt % of a copper ion precursor compound, an acid-containing stabilizer and an alcohol-containing diluent, and 60-98 wt % of water, based on the total weight of the coating composition.
44. The coating composition according to claim 43, characterized in that The coating composition comprises 0.9-1.2 wt % of titanium alkoxide.
45. The coating composition according to claim 43, characterized in that The coating composition comprises 0.05-1.2 wt % of a copper ion precursor compound.
46. A method for preparing a coating composition according to any one of claims 7 to 45, comprising: (1) preparing a solution comprising titanium alkoxide and a diluent; (2) preparing a solution comprising a copper precursor compound and a diluent, and (3) mixing the two solutions to obtain a composite precursor mixture, wherein the pH of the solution is controlled within the range of 0.1-6 in the above steps (1) and (2), and the solution in steps (1) and (2) substantially does not contain water; wherein the “substantially does not contain water” means that the solution contains less than 0.1 wt % of water based on the total weight of the solution.
47. The method according to claim 46, characterized in that A stabilizer is added in at least one of steps (1) to (3).
48. The method according to claim 47, characterized in that A stabilizer is added in steps (1) and (2).
49. The method according to claim 47, characterized in that A stabilizer comprising an acid is added in at least one of steps (1) to (3).
50. The method according to claim 46, characterized in that Acetylacetone was added.
51. The method according to claim 50, characterized in that In step (3), acetylacetone is added.
52. A method for preparing a titanium dioxide coating on a substrate, comprising: (1) applying the coating composition according to claim 7 or the coating composition prepared according to the method according to claim 46 to a substrate, and (2) raising the temperature to cure the applied coating composition.
53. A method according to claim 52, wherein curing is carried out at a temperature below 450°C.
54. A method according to claim 53, wherein curing is carried out at a temperature of 350 to 420°C.
55. A method according to any one of claims 52 to 54, wherein the coating composition is applied to the substrate by spraying in the form of an aqueous solution.
56. The method according to any one of claims 52 to 54, wherein the substrate comprises glass, ceramic and / or various inorganic composite materials.
57. An article comprising the titanium dioxide coating of claim 1, wherein the article comprises a display screen in a public place, a computer screen, a mobile phone screen, or a touch surface of an electronic device in a hospital.
Citation Information
Patent Citations
Copper-doped titanium dioxide coating and preparation method thereof
CN105733322A
A surface coating
CN106102466A
Preparation method of copper-doped titanium dioxide photocatalyst
CN111013586A
Super-hydrophilic anti-fog coating as well as preparation method and application thereof
CN111057998A
Photocatalytic coating and method for cleaning spacecraft surfaces
US6537379B1